2007
DOI: 10.1073/pnas.0702560104
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative characterization of cell synchronization in yeast

Abstract: Metabolic oscillations in baker's yeast serve as a model system for synchronization of biochemical oscillations. Despite widespread interest, the complexity of the phenomenon has been an obstacle for a quantitative understanding of the cell synchronization process. In particular, when two yeast cell populations oscillating 180°out of phase are mixed, it appears as if the synchronization dynamics is too fast to be explained. We have probed the synchronization dynamics by forcing experiments in an open-flow reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 27 publications
1
38
0
Order By: Relevance
“…Oscillations in yeast cells, 1 amoebae Dictyostelium discoideum 2 and pancreatic islets 3 were studied for their regulatory action. Furthermore, spontaneous Ca 2+ oscillation regulates neuronal cell growth, axon outgrowth, and differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Oscillations in yeast cells, 1 amoebae Dictyostelium discoideum 2 and pancreatic islets 3 were studied for their regulatory action. Furthermore, spontaneous Ca 2+ oscillation regulates neuronal cell growth, axon outgrowth, and differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Various experiments demonstrated that acetaldehyde had a very strong synchronization effect on a suspension of yeast cells [8]. However, these studies do not exclude the possibility that extracellular nucleotides such as ATP and ADP can play an important role in synchronization of glycolytic oscillations in yeast cells.…”
Section: Introductionmentioning
confidence: 98%
“…It is well known that glycolytic oscillations initiate synchronization under the densely populated condition [3]- [8]. Considering that high population densities mean intense coupling between cells, it is thought that collective properties of synchronization in glycolytic oscillations is triggered by the increase in such parameters as the diffusion coefficient d F , the volumetric ratio of the cell to the compartment φ, the kinetic constant relating to the permeability κ, and so on.…”
Section: Dependencies On Diffusion Coefficient and Cell Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…The synchronization of glycolytic oscillation within a cell population is believed to be related to the cell-cell communication with acetaldehyde (Aca) [17][18][19]. Respiratory oscillation may be, suggested by some experiments, closely related to the hydrogen sulfide mediation within the population [5,7,8].…”
Section: Introduction: Oscillation and Synchr-onization In Biomoleculmentioning
confidence: 99%